Opening a next‐generation black box: Ecological trends for hundreds of species‐like taxa uncovered within a single bacterial >99% 16S rRNA operational taxonomic unit. (22nd June 2021) - Hahn, Martin W.; Huemer, Andrea; Pitt, Alexandra; Hoetzinger, Matthias
Abstract: Current knowledge on environmental distribution and taxon richness of free‐living bacteria is mainly based on cultivation‐independent investigations employing 16S rRNA gene sequencing methods. Yet, 16S rRNA genes are evolutionarily rather conserved, resulting in limited taxonomic and ecological resolutions provided by this marker. The faster evolving protein‐encoding gene priB was used to reveal ecological patterns hidden within a single operational taxonomic unit (OTU) defined by >99% 16S rRNA sequence similarity. The studied subcluster PnecC of the genus Polynucleobacter represents a ubiquitous group of abundant freshwater bacteria with cosmopolitan distribution, which is very frequently detected by diversity surveys of freshwater systems. Based on genome taxonomy and a large set of genome sequences, a sequence similarity threshold for delineation of species‐like taxa could be established. In total, 600 species‐like taxa were detected in 99 freshwater habitats scattered across three regions representing a latitudinal range of 3, 400 km (42°N to 71°N) and a pH gradient of 4.2 to 8.6. In addition to the unexpectedly high richness, the increased taxonomic resolution revealed structuring of Polynucleobacter communities by a couple of macroecological trends, which was previously only demonstrated for phylogenetically much broader groups of bacteria. An unexpected pattern was the almost complete compositional separation of Polynucleobacter communities of Ca 2+ ‐rich and Ca 2+ ‐poor habitats. This compositional pattern strongly resembled the vicariance of plant species on silicate and limestone soils. The new cultivation‐independent approach presented opened a window to an incredible, previously unseen diversity, and enables investigations aiming on deeper understanding of how environmental conditions shape bacterial communities and drive evolution of free‐living bacteria.